BS EN 13501-3. Fire classification of construction products and building elements. Part 3. Classification using data from fire resistance tests on products and elements used in building service installations: fire resisting ventilation ducts and fire dampers and/or power, control and communication cables (29th September 2023) - British Standards Institution
No abstract available